2014
DOI: 10.1097/mib.0000000000000093
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mode of Delivery on Outcomes in Patients with Perianal Crohnʼs Disease

Abstract: Introduction Crohn's disease (CD) often affects women during the reproductive years. While several studies have examined the impact of pregnancy on luminal disease, limited literature exists in those with perianal CD. Decision regarding mode of delivery is a unique challenge in such patients due to concerns regarding the effect of pelvic floor trauma during delivery on pre-existing perianal involvement. Methods We performed a retrospective chart review of CD patients with established perianal disease undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Second, this cohort was not adequately powered to examine specifically the effect of mode of delivery on women with established perianal CD. However a complementary study recently published by our group supports the safety of vaginal delivery in that cohort as well, albeit acknowledging a selection bias in the choice of mode of delivery 35 . Third, we did not have information on the indication for CS (obstetric, provider, or patient preference) or occurrence of complications such as need for episiotomy or perianal tear during vaginal delivery and post-operative complications in the CS group.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Second, this cohort was not adequately powered to examine specifically the effect of mode of delivery on women with established perianal CD. However a complementary study recently published by our group supports the safety of vaginal delivery in that cohort as well, albeit acknowledging a selection bias in the choice of mode of delivery 35 . Third, we did not have information on the indication for CS (obstetric, provider, or patient preference) or occurrence of complications such as need for episiotomy or perianal tear during vaginal delivery and post-operative complications in the CS group.…”
Section: Discussionmentioning
confidence: 54%
“…from the Netherlands identified no increase in risk of progression to perianal involvement in CD patients without perianal disease prior to pregnancy for vaginal compared with CS delivery (5% vs. 14%, p=NS) 26 . We have recently described that vaginal delivery may be safe in women with perianal disease and not associated with short-term increase in risk of complications, albeit acknowledging a selection bias in women trialing a vaginal birth 35 . We extend the findings of that study to this larger cohort without perianal disease prior to delivery and provide reassuring data that in a wider population of CD, vaginal delivery does not appear associated with an increase in incidence of perianal or other complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a paucity of data to support actual harm from vaginal deliveries in CD women with inactive perianal disease (14). In a retrospective study of women with history of perianal disease, Cheng et al showed there was no difference in worsening of perianal symptoms between those who had vaginal and Cesarean delivery (15). Current guidelines recommend Cesarean delivery for CD only in the presence of active perianal disease, not inactive disease (5).…”
Section: Discussionmentioning
confidence: 99%
“…The indication for these deliveries diverges from current guidelines, though the extent of divergence appears consistent with other recent findings of cesarean delivery for IBD. In a recent study by Cheng et al 24 50 (82%) of 61 patients with perianal CD underwent cesarean delivery, though only three were noted to have active perianal disease during pregnancy. This data provides a real-world assessment of adherence to delivery guidelines in IBD.…”
Section: Discussionmentioning
confidence: 95%